2009
DOI: 10.3136/fstr.15.423
|View full text |Cite
|
Sign up to set email alerts
|

Anti-allergic Effects of Extracts from Commercial Products of Cooked Burdock

Abstract: The anti-allergic effects of commercial products from cooked burdock (burdock salad, fried up burdock and burdock boiled with vinegar) were investigated by analyzing their inhibitory effects on the enzymatic activity (cyclooxygenase-2, lipoxygenase, phospholipase A 2 and hyaluronidase) and the suppression of degranulation from rat basophilic leukemia (RBL)-2H3 cells. The methanol extract of burdock boiled with vinegar did not inhibit the cyclooxygenase-2 activity in the experiments. Those of the burdock salad … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
0
9
0
1
Order By: Relevance
“…Nordihydroguaiaretic acid, an IC 50 (the concentration of the extract required to inhibit 50% of the enzyme activity) value of 127.04 ± 8.40 μg·mL −1 , was used as a positive control. Studies carried out so far have shown that, as a raw material, burdock weakly inhibits lipoxygenase activity, with the IC 50 value of 0.99 mg·mL −1 [ 54 ]. Moreover, Chagas-Paula et al (2015) tested the ability to inhibit potato 5-lipoxygenase activity by 70% ethanolic extract from Arctium lappa leaves.…”
Section: Resultsmentioning
confidence: 99%
“…Nordihydroguaiaretic acid, an IC 50 (the concentration of the extract required to inhibit 50% of the enzyme activity) value of 127.04 ± 8.40 μg·mL −1 , was used as a positive control. Studies carried out so far have shown that, as a raw material, burdock weakly inhibits lipoxygenase activity, with the IC 50 value of 0.99 mg·mL −1 [ 54 ]. Moreover, Chagas-Paula et al (2015) tested the ability to inhibit potato 5-lipoxygenase activity by 70% ethanolic extract from Arctium lappa leaves.…”
Section: Resultsmentioning
confidence: 99%
“…The amount of β-hexosaminidase release by basophilic leukemia cells (RBL-2H3) was determined using a previous method with some modifications (Sato, Shinozaki et al, 2014;Sato, Yamagami, & Tamura, 2012;Sugiura, Torii, Matsuda, & Yamada, 2009). RBL-2H3 was obtained from RIKEN BioResource Center Cell Bank (Ibaraki, Japan).…”
Section: β-Hexosaminidase Release Assay Of Rbl-2h3 Cellsmentioning
confidence: 99%
“…E. stolonifera is known to produce a functional polysaccharide, alginate (Kuda et al, 2007), which inhibits HA activity (Asada et al, 1997). Interestingly, the PVPP residue did not inhibit the HA activity in by measuring the β-Hex activity as described in a previous report (Sugiura et al, 2009a). Experimental conditions for cell stimulation and exposure to tested samples was as follows.…”
Section: Removal Of Phenolic Compounds (Phlorotannins) Included In Thmentioning
confidence: 99%
“…RBL cells were cultured as described elsewhere (Sugiura et al, 2009a). Since the extent of degranulation from the mast cells is proportional to that of β-hexosaminidase (β-Hex; equivalent to histamine) (Schwartz et al, 1981), the degranulation assay by stimulated RBL cells was conducted chased from Marumo-mogami Store Co., Ltd. in Aomori Prefecture.…”
Section: Assay For Suppression Of Degranulation From Rbl-2h3 Cells Anmentioning
confidence: 99%